The Impact Of Using Binahong Leaves Extract On Flour Based Cendol - Wirnelis Syarif; Ilham Tri Wahyudi (Universitas Negeri Padang, 2021)
This research is motivated by the lack of utilization of Binahng leaves in the field of food processing. Binahong leaves are creeping plants that easily live in lowlands and highlands and still grow wild and there is no further use and cultivation by the community. Biinahong leaves have many benefits in the health sector such as normalizing blood circulation, preventing stroke, gout, ulcers, ambient, and so on. The development of binahong leaves in cendol production is expected to be able to provide delicious and healthy cendol qualities for the community. This study aims to analyze the effect of 0%, 25%, 50%, 75% and 100% substitution leaves binohong on the quality of shape, color, aroma, texture, and taste of cendol. This type of pure experimental research with a completely randomized design method. The dependent variable is the quality of cendol skin using primary data sourced from 5 expert panelists by proposing an organoleptic test format. Analysis of data with ANOVA, if Fcount> Ftable then proceed with the Duncan test. The results showed that there was a significant effect of binahong leaf substitution on the quality of color, aroma, and texture of cendol because Fcount> Ftable, and there was an insignificant effect of binahong leaf substitution on the quality of cendol flavor because Fcount <Ftable. The best results are found in the substitution of 25% and 100% for the cendol color, 50% for the cendol aroma, and 50%, 75%, and 100% for the cendol texture.